The Development of a Model to Predict the Likelihood of a Firm to Hedge Against Longevity Risk - Schoinohoritis, Panagiotis (2009)
“Alec Holden, who in April 1997 walked in his book‐marker and bet £100 he would live to 100, collected £25,000 when he reached his centenary on 24 April 2007. William Hill, which operates a chain of betting shops in the U.K., has raised the target age for such wagers to 110 years from 100” (Kabbaj & Coughlan, 2007, p.26). This is a typical example of longevity risk and the entities that are mainlyexposed to it are pension fund providers and life assurance companies. Decades of inaccurate life expectancy projections as well as surprising improvements in longevity have resulted today to vast deficits in pension funds and trillions of GBP in assets exposed to longevity risk. Hedging instruments against it are still in theoretical stage or are newly developed, while companies have only recently started to consider the existence of that risk. This study attempts to reveal which and how a firm’s characteristics might be responsible for the adoption of hedging against longevity risk. Therefore a model is theoretically developed to predict the probability that a company is likely to hedge.